Experimental investigation on combustion and emission characteristics of a premixed flame in a gas-turbine combustor with a vortex generator. (25th February 2015) - Kim, Gu; Lee, Young Duk; Sohn, Chae Hoon; Choi, Keun Won; Kim, Han Seok
Abstract: An experimental study has been carried out to investigate how a vortex generator affects the combustion and emission characteristics of a swirl-stabilized premixed flame in a gas-turbine combustor. In the experimental analyses, the chemiluminescence signals of OH radicals and gas emissions were measured for various operating conditions, both with and without the vortex generator, and the data were used to compare the two cases. When the vortex generator was equipped within a combustor and the combustor operated at design operating conditions, the OH radical signal showed broader distribution near the flame, with a 9.5% increase in maximum thickness and over 200% increase in overall area, indicating that the vortex generator stimulates chemical reactions to occur with greater spatial distribution. The gas emission measurement results also revealed that the vortex generator can reduce harmful gaseous emissions: it produced a 21.2% decrease in NOx emissions and 13.3% decrease in CO emissions. However, the results were found to differ for various off-design operating conditions, so it could be concluded that the vortex generator positively affects combustion and emission characteristics only when a sufficiently high flow velocity is maintained within the combustor; otherwise the vortex generator has a slightly negative effect. Highlights: The effects of a vortex generator on a gas-turbine combustor have been investigated. A small-scale combustor is designed and used for the analyses and experiments. Experimental work shows that NOx and CO emissions can be reduced effectively. A numerical study reveals that the vortex generator improves mixing characteristics.